Chinese investments in Greenland: Origins, progress and actors - Jiang Yang (Danish Institute for International Studies (DIIS), 2021)
Greenland is important to Denmark's position in international politics, and it has become an arena of increasing competition between great powers. Of all China's shipping, investment and scientific exploration activities in the Arctic, Chinese investments in Greenland have become the most controversial issue. For Washington DC, Copenhagen, and the IA Party that won the Greenlandic general election in April 2021, China's political influence and the environmental impacts that might come with investment are a major concern. Behind the concern is the view that Chinese investments are driven and coordinated by the Chinese state for strategic purposes, but there is a lack of studies on how close state-business relations are and to what extent the domestic reforms in China have pushed Chinese companies to seek out Greenland. Therefore, this DIIS report seeks to inform debates around the role of China in Greenland by delving into the following questions: Why would Chinese companies invest in mining projects in Greenland, and how have they obtained access? How have the projects progressed? To what extent have Chinese state actors participated in these projects?
Keywords: 300